Adaptation to the deep-sea hydrothermal vents and cold seeps: Insights from the transcriptomes of Alvinocaris longirostris in both environments. (May 2018) - Hui, Min; Cheng, Jiao; Sha, Zhongli
Abstract: Alvinocaris longirostris Kikuchi and Ohta, 1995 is one of the few species co-distributed in deep-sea hydrothermal vent and cold seep environments. We performed the transcriptome analysis for A. longirostris and identified differentially expressed genes (DEGs) between samples from the Iheya North hydrothermal vent (HV) and a methane seep in the South China Sea (MS). From the 57, 801 annotated unigenes, multi-copies of enzyme family members for eliminating toxic xenobiotics were isolated and seven putatively duplicated gene clusters of cytochrome P450s were discovered, which may contribute to adaptation to the harsh conditions. Eight single amino acid substitutions of a Rhodopsin gene with low expression in two deep-sea alvinocaridid species were positively selected when compared with shallow water shrimps, which may be the result of adaptation to the dim-light environment in deep sea. 408 DEGs were identified with 53 and 355 up-regulated in HV and MS, respectively. Various genes associated with sulfur metabolism, detoxification and mitochondria were included, revealing different mechanisms of adaptation to the two types of extreme environments. All results are expected to serve as important basis for the further study. Highlights: Transcriptomes of A. longirostris co-distributing in deep-sea hydrothermal vent and cold seep environments are compared. Molecular basis for adaptation to the chemosynthetic ecosystems in the shrimps are revealed. Positive selection in the Rhodopsin gene with low expression is found in the deep-sea shrimps.